2018
DOI: 10.1538/expanim.17-0101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of triclosan on acute toxicity, genetic toxicity and oxidative stress in goldfish (<i>Carassius auratus</i>)

Abstract: Triclosan (TCS) is used as an antimicrobial agent and has been widely dispersed and detected in the aquatic environment. However, it remains uncertain whether TCS is genotoxic or not. In this study, the acute toxicity of TCS in goldfish ( Carassius auratus ) was studied. Then, based on the results for acute toxicity, other goldfish were exposed to various concentrations of TCS (control, DMSO control, and 1/4, 1/2, and 1/8 LC 50 ) for 14 days, and the effects on gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 39 publications
2
18
0
2
Order By: Relevance
“…More recently, our previous study also confirmed that TCS could increase the antioxidant enzyme of CAT and the GSH contents and that it even induced excessive ROS production and DNA damage in the liver of goldfish after 14 d of exposure. These findings suggest that subchronic TCS concentrations can lead to oxidative damage in goldfish (Carassius auratus) [43].…”
Section: Introductionmentioning
confidence: 81%
“…More recently, our previous study also confirmed that TCS could increase the antioxidant enzyme of CAT and the GSH contents and that it even induced excessive ROS production and DNA damage in the liver of goldfish after 14 d of exposure. These findings suggest that subchronic TCS concentrations can lead to oxidative damage in goldfish (Carassius auratus) [43].…”
Section: Introductionmentioning
confidence: 81%
“…Additionally, several freshwater species commonly held as pet aquarium fish such as gold fish (Carassius auratus) [172][173][174][175][176] and guppies (Poecilia reticulate and Poecilia vivipara) [177][178][179][180] are also used for the assessment of DNA damage using the comet assay.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…TCS-mediated production of reactive oxygen species (ROS) causes oxidative stress and may lead to DNA damage. TCS was found to induce oxidative stress and genotoxic response in goldfish [6], was associated with oxidative stress, and activated the antioxidant system in Trissolcus japonicas [7]. Further, TCS is thought to exert potential biochemical and genetic toxicities in Eisenia fetida [8].…”
Section: Introductionmentioning
confidence: 99%